Reviews and Abstracts [review of "Reflectarray antennas (Huang, J. and Encinar, J.A.; 2008)] - Pozar, David (IEEE antennas & propagation magazine, 2008)
This book gives a very thorough and complete exposition of the history, theory and analysis, and practical design of printed reflectarray antennas. It will be useful to both experienced workers in the field as well as to students or engineers new to the subject.